2010
DOI: 10.1016/j.snb.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

An intracellular glucose biosensor based on nanoflake ZnO

Abstract: Abstract:In this study, a potentiometric intracellular glucose biosensor was fabricated by immobilization of glucose oxidase on nanoflake ZnO. Nanoflake ZnO with a wall thickness around 200 nm was grown on the tip of a borosilicate glass capillary and used as a selective intracellular glucose biosensor for the measurement of glucose concentrations in human adipocytes and frog oocytes. The results showed a fast response within 4 s and a logarithmic linear glucose-dependent electrochemical potential difference o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 51 publications
0
80
0
1
Order By: Relevance
“…The effect of the coupling agents, (3-aminopropyl) trimethoxysilane, (3-aminopropyl) triethoxysilane, and (3-aminopropyl) methyldiethoxysilane (APS), on the covalent immobilization of GOx on ZnO nanorods was studied [36]. The APS-treated glucose sensor exhibited the highest sensitivity and lowest K M app , which was attributed to the APS-treated ZnO nanowires containing the largest number of C-N Immobilizing GOx on more complex ZnO nanostructures as working electrodes to detect glucose has also been investigated [12,[37][38][39][40][41][42][43]. Yang et al [37] prepared a highly oriented single-crystal ZnO nanotube array (Fig.…”
Section: Science China Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the coupling agents, (3-aminopropyl) trimethoxysilane, (3-aminopropyl) triethoxysilane, and (3-aminopropyl) methyldiethoxysilane (APS), on the covalent immobilization of GOx on ZnO nanorods was studied [36]. The APS-treated glucose sensor exhibited the highest sensitivity and lowest K M app , which was attributed to the APS-treated ZnO nanowires containing the largest number of C-N Immobilizing GOx on more complex ZnO nanostructures as working electrodes to detect glucose has also been investigated [12,[37][38][39][40][41][42][43]. Yang et al [37] prepared a highly oriented single-crystal ZnO nanotube array (Fig.…”
Section: Science China Materialsmentioning
confidence: 99%
“…For a practical serum sample, the biosensors exhibited good accuracy and practicability, with recoveries of 95%-103%. A potentiometric intracellular glucose biosensor was fabricated, by immobilizing GOx on nanoflake ZnO grown on the tip of a borosilicate glass capillary [40]. The nanoflake ZnO (Fig.…”
Section: Science China Materialsmentioning
confidence: 99%
“…A considerable amount of literature has been published on ZnO nanostructure in sensors, such as glucose sensor (Fulati et al 2010;Usman Ali et al 2010), ultraviolet detector (Chai et al 2009;Foo et al 2013b) and chemical and gas sensors Kashif et al 2013a). However, ZnO nanostructure with its high isoelectric point (IEP) is the main feature for the low isoelectric point of DNA to immobilize on ZnO nanostructure surface through electrostatic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO nanoflake structures possess lots of interesting unique proper ties such as porous structures and large surface areas. It is reported that sensors based on ZnO nanoflake structures have an improved performance and a higher sensitivity compared to ZnO nanorods/nanowires 15) . To synthesize uniform nanosized ZnO particles and control their sizes and morphology, a variety of techniques have been used such as thermal oxidation of metallic zinc, hydrothermal methods, plasma chemical synthesis, laser ablation and vapor condensation [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%